High Prevalence of Hepatitis C Virus Type 5 in Central France Evidenced by a Prospective Study from 1996 to 2002 - Henquell, Cécile (American Society for Microbiology, 2004)
From 1996 to 2002, hepatitis C virus (HCV) typing was prospectively performed for 1,281 unselected HCV-infected and viremic patients, irrespective of their clinical status. Eighty-three patients (6.5%) were coinfected with human immunodeficiency virus (HIV) and HCV. A total of 1,195 strains were identified by a serotype screening (Murex HCV Serotyping 1-6 assay) and/or genotyping (Inno-LiPA HCV II) test. The distribution of HCV types showed an unusually high rate of type 5 (14.2%) that was stable over time and was the third most frequent type, after type 1 (59.1%) and type 3 (15.1%). HCV type 5 was more frequent in patients who were older than 50 (P = 10(−6)), but its frequency did not differ significantly by gender (P = 0.21). Serotyping was performed for 1,160 strains but failed for 30.2% of them. The efficiency depended on HIV status (for HCV-HIV-coinfected patients, half of the strains were untypeable) and HCV type. Genotyping was performed for 428 samples, with an overall efficiency of 99.3%. It failed in three cases, which were subsequently identified as HCV type 2. Serotyping and genotyping results for 39 patients showed discrepancies between the two methods for 4 patients, who had HCV type 2, type 6, or mixed infections. Thus, HCV type 5 may also be encountered frequently in Western countries. Its apparent confinement to a restricted area raises the question of how it emerged and underscores the need for further studies of HCV type prevalence, routes of transmission, pathogenicity, and responses to treatment.